Estimation of areas occupied by winter field crops in Uruguay using remote sensing - Giménez, Agustín; Pedro Castaño, José (Revista Mexicana de Ciencias Agrícolas, 2018)
One of the most important factors of risk in agricultural production consists of adverse climate events (droughts, floods, ground frost, etc.), related to climate change and variability. A modern “adaptation” approach for coping with adverse climate events is to develop and implement anticipatory actions commonly named “risk management” strategies. To develop this kind of strategies, reliable and updated information on land use, location of agricultural areas, and crop status monitoring is crucial. The aim of this work was to explore the use of Landsat satellite images to locate and estimate winter field crop areas in the livestock agriculture production region of Uruguay. The study area was composed of the Departments of Colonia, Soriano and Río Negro. To estimate the surface occupied by winter field crops, six Landsat 5 TM images were processed, using the ERDAS Imagine software, running the “supervised classification” method, and modeling multi temporal analyses. The estimation based on satellite image processing largely showed the results of the National Agricultural Census for the year 2000. These results lead to conclude that the use of remote sensing with satellite images is a tool of great potential and use for mapping and monitoring land use in Uruguay, contributing to the preservation of natural resources and ecosystems.
Keywords: Landsat; remote sensing; winter field crops; land use